A case study on the Consecration of Space at Mahidol University Salaya Campus - Dillon, Jane (Poligrafi, 2022)
This article presents the phenomenon of religious revival in the twentieth century through a case study of phenomenology at Mahidol University Salaya campus, Thailand. The principal scope of this study is on the socio-religious construct of the contemporary Buddhist community at Mahidol University Salaya campus. The revival of religion at the university has transformed the campus into a religious space that juxtapositions its secular academic framework.